Sosialisasi Tentang Solusi Penataan Dan Pengelolaan Bumdes Pada Desa Bipolo - Mathelda Naatonis (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
The crucial problem in BUMDes is the arrangement and management of BUMDes. This service aims to provide solutions for the management of BUMDes Bipolo to create quality BUMDes governance. The service method is carried out through lectures to BUMDes administrators. The results of the service found that the solution in structuring and managing BUMDes consists of first, the need for education and training for BUMDes administrators in organizing and managing BUMDes, second, business management in BUMDes must be carried out in principle in order to generate selling value from BUMDes, and third, the financial capacity of BUMDes which is based on the success of BUMDes in creating a conducive and profitable financial situation for BUMDes.